Natural Products as New Approaches for Treating Bladder Cancer: From Traditional Medicine to Novel Drug Discovery - Yoo Kang; Chelin Park; Heemin Lee; Sojin Kang; Chunhoo Cheon; Bonglee Kim (MDPI AG, 2023)
Bladder cancer (BC) is a heterogeneous disease that a tumor develops in the bladder lining and in some cases, the bladder muscle. Chemotherapy and immunotherapy are commonly used to treat bladder cancer. However, chemotherapy can cause burning and irritation in the bladder while BCG immunotherapy, which is the main type of intravesical immunotherapy for bladder cancer, can also cause burning in the bladder and flu-like symptoms. Thus, drugs originating from natural products have attracted much attention due to the reports that they have anti-cancer properties with low adverse effects. In this study, eighty-seven papers that dealt with natural products preventing or treating bladder cancer were reviewed. The studies were classified into the following mechanism: 71 papers on cell death, 5 papers on anti-metastasis, 3 papers on anti-angiogenesis, 1 paper on anti-resistance, and 7 papers on clinical trials. Most of the natural products that induced apoptosis up-regulated proteins such as caspase-3 and caspase-9. Regarding anti-metastasis, MMP-2 and MMP-9 are regulated frequently. Regarding anti-angiogenesis, HIF-1α and VEGF-A are down-regulated frequently. Nevertheless, the number of papers regarding anti-resistance and clinical trial are too few, so more studies are needed. In conclusion, this database will be useful for future in vivo studies of the anti-bladder cancer effect of natural products, in the process of selecting materials used for the experiment.